An experimental study of multicolored composite yarns for woven fabrics by the friction spinning method. Issue 4 (March 2016) - Hua, Tao; Lo, Wing Wai; Xiao, Xueliang
This paper presents a fabrication method for multicolored composite yarn based on a tri-coaxial yarn architecture by using a friction spinning machine. The yarn consists of a core, intermediate layer and outer layer in a coaxial form for accommodating fibers in different colors. The influence of fiber weight ratio of the intermediate layer to outer layer on yarn structure in terms of fiber coverage for each layer as well as yarn properties was investigated to identify the appropriate fiber weight ratio for yarn production. The results from the experiments show that the magnitude of fiber coverage of the intermediate layer on the yarn core increases with the increase of fiber weight ratio, while the fiber coverage performance of the outer layer on the intermediate layer of the yarn becomes better when a lower fiber weight ratio is adopted. The fiber weight ratio also has an effect on the yarn properties, including strength and elongation, hairiness, evenness and imperfection. Based on the evaluation of yarn structure and properties, a fiber weight ratio of 0.50 was selected to produce the multicolored composite yarns for woven fabrics. A weft-faced woven fabric was produced by using the developed multicolored composite yarns as weft yarns. Then, the laser engraving treatment with appropriate laser fluence from a feasible working range of both laser resolution and pixel time was applied to woven fabric to create a multicolor effect. The treated woven fabric exhibits a unique pattern effect using the developed multicolored effect composite yarns.